PENDIDIKAN AGAMA ISLAM DAN ISU KEKERASAN DALAM HAK ASASI MANUSIA - Sukirman Sukirman; Masnun Baiti; Syarnubi Syarnubi (PAI RAFAH, 2023)
Indonesia is currently faced with a moral crisis. One form of moral crisis is violence and human rights in schools. Such as acts of revenge that lead to tauran between students. This event occurred because of the failure of the implementation of religious education in schools including Islamic religious education (PAI). This failure occurs one of them due to the PAI taught in schools today in practice prioritizes the cognitive aspect alone and ignores the affective aspect as well as the lack of growing determination to cultivate religious values. In other words, religious education is less oriented towards learning about religion and less oriented towards the right way of religion. As a result, there is a gap between knowledge and practice in the life of religious values. In practice, religious education has not become religious teaching so that it is unable to form moral individuals, even though the core of religious education is moral education. In overcoming the above problems, the contribution of PAI is the development of human mentality which is its product by preparing PAI materials as the first step in instilling children's morals In analyzing the PAI material, the author uses Brunner's theory, namely the spiral curriculum which consists of elements of facts, concepts, procedures, principles and values/affective or motoric. The focus of the material analysis conducted by the author is the subject matter of Al-Qur'an Hadith, Fiqh and Akidah Akhlak and SKI at the MI / SD level.